HUBUNGAN ANTARA KECERDASAN EMOSIONAL (EMOTIONAL QUOTIENT) DENGAN HASIL BELAJAR SISWA SEKOLAH DASAR GUGUS VII KECAMATAN TAMPAN PEKANBARU (STUDI KORELASIONAL PADA SISWA KELAS V SEKOLAH DASAR GUGUS VII KECAMATAN TAMPAN PEKANBARU) - Gustini, Geni; Noviana, Eddy; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine between emotional quotient and the studentd’s learning of primary school Tampan, Pekanbaru. The population in this study was 332 students in class V of primary school Tampan, Pekanbaru, 92 students were taken as sanple by using sampling pusposive technique. The method was chi square correlation that used to see the relation between variable emotional quotient and variable the learning. The data collection that technique used large-scale testing and analysis of statistical methods that was SPSS for Windows Ver.17. Based on the result by testing the hypothesis, there is no significant relationship between emotional quotientand learning of primary school students Tampan Pekanbaru. It can be seen from the number of corralation coefficient 0.301 and taraf of the significant 8.7555 <9.488. The level of relationship between emotional quotient and learning can be categorized in to low category with 9.06% as the coefficient of determination, that means emotional quotient has a big influence as much as 9.06% on the student’s learning of primary school gugus VII Tampan Pekanbaru.Keywords: Emotional Quotient, Learning Outcomes